2021
DOI: 10.1021/acs.jpcc.1c06979
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rotational Motion of Nitroxides on Overhauser Dynamic Nuclear Polarization: A Systematic Study at High Magnetic Fields

Abstract: TEMPOL nitroxide radicals are frequently used as a polarizing agent for liquid-state Overhauser dynamic nuclear polarization. To achieve large signal enhancements at high magnetic fields (9.4 T), fast picosecond to sub-picosecond dynamics between nitroxide and the target solvent molecule are required. Such dynamics have been predicted by molecular dynamic studies and attributed to fast inner-sphere motions of a transient radical–solvent complex. Here, we systematically study a series of nitroxide radicals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…We also show that the values of ⟨ r –6 ⟩ norm and ϕ ENS calculated from the one-field fitting procedure we developed previously are in excellent agreement with those calculated using the extended spectral densities, thereby demonstrating that, in practice, one set of 1 H-Γ 1 and 1 H-Γ 2 measurements at a single spectrometer frequency is sufficient to obtain accurate values of ⟨ r –6 ⟩ norm and ϕ ENS . Furthermore, we show that ⟨ r –6 ⟩ norm obtained using our Ansatz spectral density function is in excellent agreement with that obtained by the “standard” fitting procedure used to analyze NMRD and Overhauser dynamic nuclear polarization (DNP) data. Finally, we demonstrate that the scaling property provides a simple and convenient way to extract multiple J (ω H ) values using a single spectrometer field, thereby affording a more accurate experimental determination of ⟨ r –6 ⟩ norm .…”
Section: Introductionsupporting
confidence: 69%
“…We also show that the values of ⟨ r –6 ⟩ norm and ϕ ENS calculated from the one-field fitting procedure we developed previously are in excellent agreement with those calculated using the extended spectral densities, thereby demonstrating that, in practice, one set of 1 H-Γ 1 and 1 H-Γ 2 measurements at a single spectrometer frequency is sufficient to obtain accurate values of ⟨ r –6 ⟩ norm and ϕ ENS . Furthermore, we show that ⟨ r –6 ⟩ norm obtained using our Ansatz spectral density function is in excellent agreement with that obtained by the “standard” fitting procedure used to analyze NMRD and Overhauser dynamic nuclear polarization (DNP) data. Finally, we demonstrate that the scaling property provides a simple and convenient way to extract multiple J (ω H ) values using a single spectrometer field, thereby affording a more accurate experimental determination of ⟨ r –6 ⟩ norm .…”
Section: Introductionsupporting
confidence: 69%
“…It should be noted that the negative OE in the middle of the field profile was absent, but usually the OE is much less efficient at high magnetic fields for bulky polarizing agents and viscous liquids. 49 The SE mechanism was confirmed by both the displacement of both positive and negative peaks in the DNP field profile by ±ω H /γ e , compared to the EPR resonance position, and the similar widths of the peaks in the DNP field profile and the EPR spectra of the polarizing agents. The SE mechanism is based on the excitation of forbidden zeroquantum and double-quantum transitions in a coupled electron−nuclear spin system.…”
Section: ■ Discussionmentioning
confidence: 84%
“…Our near-physiological temperature DNP experiments in a magnetic field of 9.4 T clearly revealed that only one mechanism was operational in polarization transfer, namely, the SE. It should be noted that the negative OE in the middle of the field profile was absent, but usually the OE is much less efficient at high magnetic fields for bulky polarizing agents and viscous liquids . The SE mechanism was confirmed by both the displacement of both positive and negative peaks in the DNP field profile by ±ω H /γ e , compared to the EPR resonance position, and the similar widths of the peaks in the DNP field profile and the EPR spectra of the polarizing agents.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the dipolar Overhauser effect (as in the case of 1 H) has only limited applications owing to low DNP efficiency at high magnetic fields. 35,36 Therefore, to increase the 1 H polarization, a technique was proposed recently for transferring 13 C hyperpolarization produced by scalar Overhauser DNP to the attached 1 H spins via the polarization transfer scheme. 37,38 With regard to an intermediate state between solids and liquids, viscous media, only a few DNP measurements at high magnetic fields 39,40 and a number of DNP experiments at low magnetic fields exist.…”
mentioning
confidence: 99%
“…If the scalar coupling dominates over the dipolar one (as commonly observed for 13 C, 15 N, 19 F, or 31 P nuclei), then the Overhauser DNP can yield outstanding signal enhancements at magnetic fields of ≥1 T, although usually it requires specific chemical systems that involve a strong contact interaction between the electron and nuclear spins. On the other hand, the dipolar Overhauser effect (as in the case of 1 H) has only limited applications owing to low DNP efficiency at high magnetic fields. , Therefore, to increase the 1 H polarization, a technique was proposed recently for transferring 13 C hyperpolarization produced by scalar Overhauser DNP to the attached 1 H spins via the polarization transfer scheme. , …”
mentioning
confidence: 99%